The Ability of Chemistry Problem Solving of Senior High School Students in Palu Sulawesi Tengah - Ijirana Ijirana; Sitti Aminah; Supriadi Supriadi; Detris Poba (Universitas Tadulako, 2021)
The research is purposed to describe the problem-solving ability of the Senior High School XI grader students in Palu city. The measurement of the problem-solving ability could be determined by solving the exercises of Hydrocarbon and Thermochemistry topics using the Polya’s sequences; consisting of understanding the problem, devising, doing the plan, and evaluating. The ability of students’ problem solving is classified well in every sequence in case of the number of high category students is 60%. The samples are 240 of 507 XI grade students learning chemistry in SMAN 3 and SMA Madani Terpadu in Palu City. The data of problem-solving is determined by providing a test in the form of a validated assay. The result shows the average of XI graders in Palu City only capable of solving the problem without understanding, devising, and evaluating while solving hydrocarbon topics. The ability is not even possessed by students in Thermochemistry. It implies that senior high school students in Palu could not represent the problem in the form of figure, symbol, statement, and mathematics statement or have not been able to devise the problem solving and correlate the obtained result with the related theory or concept. Therefore, the students should be trained to solve the problem in learning by application the problem-solving sequences.